Teaching English Language at SSC Level in Private Non-Elite Schools in Pakistan: Practices and Problems - Muhammad Fareed; Saniya Jawed (Journal of Education and Educational Development, 2020)
English language is taught as a compulsory subject up to graduate level in Pakistani educational system. Despite studying English for over 14 years, majority of students coming from non-elite schools, lack required command in English language skills to pursue their higher education and professional careers. With this background in mind, the current research focused on teaching English reading and writing skills and the problems faced while teaching these skills at Secondary School Certificate (SSC) level in private non-elite schools in Karachi. The sample of the study comprised 20 SSC level students, 12 SSC level English language teachers of non-elite private schools and 5 student notebooks. Data were collected through open-ended questionnaires, group interviews and notebook analysis. Data were examined using thematic analysis. The findings revealed that teaching English language reading practices include reading the text aloud, translating the chapter, providing the central idea and meanings of difficult words to the students. The major problems faced by the teachers in teaching reading skills are learners’ lack of interest in reading, lack of concentration and low reading comprehension skills. The study also revealed practices of teaching writing skills such as provision of model texts and relevant vocabulary items. The major problems while teaching writing skills are lack of pre-writing activities, learners’ deficient command over vocabulary, grammar, spellings and punctuation, lengthy syllabus and limited time.
Keywords: English language teaching; reading skills; SSC level; writing skills